Mussel-inspired synthesis of magnetic N-Halamine nanoparticles for antibacterial recycling - Chai, Danxia; Liu, Wenxin; Hao, Xiufeng; Wang, Heyuan; Wang, Haixiao; Hao, Yujiao; Gao, Yue; Qu, Huihui; Wang, Lifang; Dong, Alideertu; Gao, Ge (Colloid and interface science communications, 2020)
Antibacterial N-halamine coatings are successful in avoiding and eliminating bacterial infections caused by bacterial contamination and biofilms on the surfaces. However, the N-halamine coatings remain a long-standing challenge faced by our healthcare system. Herein we reported a new mussel-inspired surface modification strategy to achieve N-halamine copolymer coatings with adhesive effects. The phenolic hydroxyl groups from N-halamine copolymers are used for ligand exchange with oleic acid on the magnetic Fe3O4 nanoparticles for binding the N-halamine copolymer onto the surface of the nanoparticles. The as-synthesized N-halamine coatings endow the magnetic Fe3O4 nanoparticles antibacterial activity toward both Gram-negative bacteria (Escherichia coli) and Gram-positive bacteria (Staphylococcus aureus). Since the super-paramagnetism of Fe3O4 in core, the N-halamine coatings are separable magnetically and remain high inactivating efficiency toward bacteria even after five cycles. We believe that, with the advantage of mussel-inspired strategy, the N-halamine coatings should have great potential for use in antibacterial and biomedical fields. [Display omitted] •A mussel-inspired synthesis for achieving N-halamine coatings is proposed.•The coating mechanism relies on the ligand exchange.•N-Halamine coatings endow good antibacterial activity and renewability.